2016
DOI: 10.1097/md.0000000000002671
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Haemophilus influenzae Serotype f Case Reports in Mazovia Province, Poland

Abstract: After successful introduction of anti-Haemophilus influenzae (Hi) serotype b vaccination program in Poland, invasive non-b or nontypeable H. influenzae infections have been reported more frequently alike in other countries all over the world. In this paper, we report 2 cases of H. influenzae serotype f (Hif) meningitis with severe clinical presentations which are rarely seen in previously healthy children.The first case is a 6-year-old girl who was admitted to pediatric ward with signs of meningitis. Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous studies [12,13] have shown that Non-type b H. influenzae infection is associated with significant morbidity in the pediatric population. The knowledge of non-type b H. influenzae as an important pathogen in the pediatric population is constantly improving.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [12,13] have shown that Non-type b H. influenzae infection is associated with significant morbidity in the pediatric population. The knowledge of non-type b H. influenzae as an important pathogen in the pediatric population is constantly improving.…”
Section: Discussionmentioning
confidence: 99%
“…Further immunocompromising conditions were not excluded in this case. 9 Infections due to invasive Hif are still rare and affect mainly vulnerable patient groups with usually favorable outcomes. Our case, with the report from Poland, raises the question of the risk for healthy children to die of fulminant diseases due to Hif.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a huge diversity of typification rates and clinical information between different countries and regions, making precise statements very difficult. [1][2][3][4][5]9 Increasing incidence of ncHi has led to several studies dealing with the development of a vaccine against unencapsulated forms of Hi. 10 Only if there is an objectified increase of invasive Hif infections with high mortality and morbidity rates, there will be efforts of implementing immunoprevention is this case as well.…”
Section: Discussionmentioning
confidence: 99%